Achievements and progress beyond the current global pandemic - Cheah, Yoke Kqueen (Life Sciences, Medicine and Biomedicine, 2021)
Life Sciences, Medicine and Biomedicine was established in 2017 as an open access, multidisciplinary, peer-reviewed journal. The journal welcomes submissions in all areas of life sciences, medicine and biomedicine with a selection of relevant biological sciences on a case by case basis. It is expected that the wide scope of the journal will promote multidisciplinary collaboration and attract research papers from diverse scientific settings. To put things into perspective, the first issue was published at the end of 2017, with four issues per year through 2018 and 2019 respectively. In 2020, the publication frequency was changed to a single issue annually, adopting to the continuous publication model practiced by many others. Manuscripts are processed for peer-review, and published as they are accepted throughout the year. This method has helped the editorial office to streamline the editorial process. Accepted articles are prepared for publication more robustly and in a timely manner. Based on this experience, the current model of continuous publication will be maintained. In addition to research and review articles, the journal also accepts submissions for mini reviews, opinion pieces and case reports. For the upcoming Volume 6 Issue 1 which will be accepting articles throughout 2022, the journal will be implementing a number of changes to the submission and editorial process. One area currently being improved is the mechanism to allow authors to submit manuscripts with very minimal formatting. Based on the feedback received from our authors, this will significantly reduce the time taken for new submissions to go through initial quality checks and approval, so that the peer-review process can commence as soon as possible. The new author’s guide will be updated and implemented in September 2021. Taking into account the global pandemic, the article processing charges for accepted manuscripts are waived throughout 2021. Further discussions are currently being held to provide financial assistance for future article processing charges for authors that may require them. Despite the challenging period the world is currently facing, the growth of the journal continues. The journal attributes this achievements to the scholarly contributions of the authors, reviewers and editors. During this similar period, the journal received successful approval for indexing with the Directory of Open Access Journals (DOAJ) and Scilit. It is also indexed in MyJurnal (Citation and Infometric Division of the Ministry of Higher Education, Malaysia). Editorial good practices will continue to be enhanced based on industry standards to ensure the journal attracts high quality scientific work. Preparation is also in progress for indexing with other major indexing organizations, which will assist authors and articles to reach a wider global audience. While the journal was initially established for the Malaysian scientific community, the current focus is for authorship and readership coverage to reach as widely as possible within the South East Asian and Asian regions. With this in mind, the expansion of the editorial board members now include experts from Malaysia, Philippines and Hong Kong. Additional editorial roles are currently being explored to complement the multidisciplinary scope of the journal, with plans for each field of research to spearhead its own section. For the journal to reach a wider global scientific community, the International Advisory Board consisting of experts from Singapore, UK, Japan, Bangladesh, China, Iraq, Philippines and Malaysia was recently established. The advisory board will provide feedback on current strategies and future direction for the international expansion of the journal, establishing good practices and will submit an annual assessment for continuous quality improvement. It is equally exciting to announce that the journal will publish a special issue this year for the Asian Conference on Biomedical Research and Laboratory Medicine 2021 organized by the Malaysian Association of Clinical Biochemist in collaboration with Malaysian Association of Biomedical Sciences and Association of Scientific Officers of the Ministry of Health, Malaysia from the 24-26 August 2021.